Andean caravan ceremonialism in the lowlands of the Atacama Desert: The Cruces de Molinos archaeological site, northern Chile. (20th November 2019) - Valenzuela, Daniela; Cartajena, Isabel; Santoro, Calogero M.; Castro, Victoria; Gayo, Eugenia M.
Abstract: Camelid caravans have played a key role in the complex systems of interregional social interaction that characterizes Andean history. In the northernmost region of Chile, the most frequent archaeological indicators of these caravan systems are trails and rock art images. Cruces de Molinos (LL-43), a rock art site in the Lluta valley, 1100 masl, 40 km from the Pacific littoral, expands the ceremonial role of rock art sites, materialized, not only as regards the iconography portrayed and alluding to these practices, but also in terms of articulated carcass remains and detached anatomical units of camelids, intentionally deposited in a cache beneath one of the engraved blocks. This paper analyzes the site considering the visual imagery, spatial location, archaeological deposits and features associated with rock art. Based on the predominance of camelid and caravan motifs in rock art images, the extraordinary setting and location of the site on the valley's upper slopes, which is far removed from local settlements, but closely connected with a llama caravan trade network linking the chaupiyunga ecozone with the highlands ( sierra and Altiplano ecozones), we suggest that Cruces de Molinos was not a rest stop for caravanners, but a ceremonial place, and not for local farmers, but for highland herders. According to seven accelerator mass spectrometry (AMS) dates that place the occupation between cal. 1060–1190 CE in the Late Intermediate period.